2016
DOI: 10.1080/10926755.2016.1149534
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Adoption and Adoption Intentions of Nonparental Caregivers

Abstract: Data from the 2011–2012 National Survey of Children’s Health and the 2013 National Survey of Children in Nonparental Care were used to fit a multinomial logistic model comparing three groups to those who never considered adoption: those who ever considered, but are not currently planning adoption; those planning adoption; and those who adopted. Adoption may be more likely when the caregiver is a nonkin foster parent, a foster care agency was involved, and/or financial assistance is available. Those with plans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 15 publications
1
7
1
Order By: Relevance
“…Indicating that some households intending to adopt a child are unable to hurdle the associated barriers to adoption compare to those with more resources which might able to hurdle. [14] Contrary to the finding in this study as it relates to marriage type (monogamy) correlating with a positive attitude towards child adoption, a survey carried out in the US reported that the unmarried caregivers were more likely to consider adoption or have current plans to adopt a child [14]. There is, therefore, a need to expand the scope of future studies in developing countries to examine factors associated with actual adoption.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Indicating that some households intending to adopt a child are unable to hurdle the associated barriers to adoption compare to those with more resources which might able to hurdle. [14] Contrary to the finding in this study as it relates to marriage type (monogamy) correlating with a positive attitude towards child adoption, a survey carried out in the US reported that the unmarried caregivers were more likely to consider adoption or have current plans to adopt a child [14]. There is, therefore, a need to expand the scope of future studies in developing countries to examine factors associated with actual adoption.…”
Section: Discussioncontrasting
confidence: 83%
“…In a study carried out in the United States of America, income and education were found to be the only significant predictors for adoption plans and though not for actual adoption. [14] A further analysis of this show that children who were adopted were less likely to live in impoverished households. Indicating that some households intending to adopt a child are unable to hurdle the associated barriers to adoption compare to those with more resources which might able to hurdle.…”
Section: Discussionmentioning
confidence: 91%
“…A considerable amount of the extant literature on adopted children is based on US samples (e.g. Wadsworth et al, 2002;Bramlett and Radel, 2016;Brodzinsky, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A considerable amount of the extant literature on adopted children is based on US samples 1 (e.g. Bramlett and Radel, 2017; Brodzinsky, 2011; Wadsworth, et al., 2002). Several European studies have emerged in recent years covering a wide range of adoption related matters, but much of this literature pays limited attention to education as a primary focus.…”
Section: Introductionmentioning
confidence: 99%
“…All of these are considered to be potential ACEs and can lead to children to being removed by child protective services (CPS). These factors could be part of the reason it is more likely that children with high ACE scores are in non‐parental care (Radel et al, 2016), which correspond with many ACE components (Bramlett & Radel, 2014). Children in non‐parental care are more likely to have mental health conditions such as depression, behaviour problems, learning disabilities and developmental delays than their peers (Radel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%